2004
DOI: 10.1111/j.1365-2044.2004.03560.x
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned admission rates and postdischarge complications in patients over the age of 70 following day case surgery

Abstract: SummaryThe elderly are a group of patients who would seem ideally suited to day surgery. However, age was initially regarded as a potential barrier to this process. We conducted a retrospective review of 1647 elderly patients (> 70 years of age) over a two-year period. Our results show a favourable outcome for these patients with low rates of unplanned admission and postoperative complications. Elderly patients seem to be at no increased risk of complications after day surgery, and show excellent satisfaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 3 publications
(5 reference statements)
0
37
1
2
Order By: Relevance
“…Our reported rate of unplanned admission in patients with a PSG (6.2%; 95% CI 5.0 to 7.4) was higher than in our general ambulatory population (2.1%; 95% CI 1.9 to 2.2) and higher than rates published from other ambulatory care centres. [17][18][19] It is unclear why patients who had previously undergone a PSG would be admitted more frequently than those who had not been tested. A review of Table 3 suggests that indications for unplanned admission were predominantly surgical or related to oxygen saturation.…”
Section: Discussionmentioning
confidence: 99%
“…Our reported rate of unplanned admission in patients with a PSG (6.2%; 95% CI 5.0 to 7.4) was higher than in our general ambulatory population (2.1%; 95% CI 1.9 to 2.2) and higher than rates published from other ambulatory care centres. [17][18][19] It is unclear why patients who had previously undergone a PSG would be admitted more frequently than those who had not been tested. A review of Table 3 suggests that indications for unplanned admission were predominantly surgical or related to oxygen saturation.…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence to suggest the age is not a barrier to day case surgery. 27 It is still important to consider any potential comorbidities particularly common in increasing age. Although we excluded women with ASA grade III or IV, it has been suggested that women with ASA III could be safely treated as day cases.…”
Section: Discussionmentioning
confidence: 99%
“…Because day case surgery accounts for an increasing proportion of surgical workload in the elderly, 9 evidence of POCD immediately after surgery may have significant implications for their suitability for day surgery and postdischarge care. Propofol and sevoflurane are commonly used anesthetic agents in everyday practice.…”
Section: Conclusion : Le Premier Jour Après Une Opération Mineure L'mentioning
confidence: 99%